2015
DOI: 10.1158/1541-7786.mcr-14-0487
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy Supports Breast Cancer Stem Cell Maintenance by Regulating IL6 Secretion

Abstract: Autophagy is a mechanism by which cells degrade cellular material to provide nutrients and energy for survival during stress. The autophagy is thought to be a critical process for cancer stem (CSC) or tumor initiating cell maintenance but the mechanisms by which autophagy supports survival of CSCs remain poorly understood. In this study, inhibition of autophagy by knockdown of ATG7 or BECN1 modified the CD44+/CD24low/− population in breast cancer cells by regulating CD24 and IL6 secretion. In a breast cancer c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
120
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 154 publications
(125 citation statements)
references
References 41 publications
5
120
0
Order By: Relevance
“…In further support of the different characteristics of the ALDH + and CD29 hi CD61 + BCSCs, we found that while it affected both BCSCs, which is consistent with a number of previous reports (20,21,40), inhibition of autophagy by FIP200 deletion compromised ALDH + and CD29 hi CD61 + BCSCs through defects in the Stat3 and TGF-β/Smad pathways, respectively. Regulation of Stat3 by autophagy in breast cancer cells have been previously reported and this can be mediated by IL-6 secretion that is controlled by autophagy related proteins (18).…”
Section: Discussionsupporting
confidence: 92%
“…In further support of the different characteristics of the ALDH + and CD29 hi CD61 + BCSCs, we found that while it affected both BCSCs, which is consistent with a number of previous reports (20,21,40), inhibition of autophagy by FIP200 deletion compromised ALDH + and CD29 hi CD61 + BCSCs through defects in the Stat3 and TGF-β/Smad pathways, respectively. Regulation of Stat3 by autophagy in breast cancer cells have been previously reported and this can be mediated by IL-6 secretion that is controlled by autophagy related proteins (18).…”
Section: Discussionsupporting
confidence: 92%
“…A previous study demonstrated that autophagy regulation has different and even opposite effects in breast cancer, indicating the need for a selection strategy when aiming to modulate autophagy in cancer therapy [30] . Interestingly, lncRNAs are reported to be critical regulators involved in tumour-related apoptosis, autophagy, and metastasis [31] .…”
Section: Discussionmentioning
confidence: 99%
“…After RNA-seq, derived sequences were analyzed by applying a custom computational pipeline that consisted of the opensource gSNAP, Cufflinks, and R for sequence alignment and ascertainment of differential gene expression. [12][13][14][15] In short, the reads generated were mapped to the human genome (hg10) by gSNAP, expression (fragments per kilobase of transcript per million mapped reads; FPKM) derived by Cufflinks, and differential expression was analyzed with analysis of variance in R. 16,17 Analyses of variance were performed to compare the expression levels of all four control subjects and all four subjects with CRS on a gene-by-gene basis. Once the gene list was formed, data were analyzed by using Ingenuity Pathway Analysis (Qiagen, Redwood City, CA).…”
Section: Resultsmentioning
confidence: 99%